Smart temperature measurement for pharmaceutical industry. Issue 3 (3rd April 2022) - Gupta, Kunal; Singh, Rishabh; Kumar, Neeraj; Sudha, K.; Panjrath, Saaransh; Tegwal, Devanshi
Abstract: It has been observed that medicines tend to change their chemical properties which makes it not fit for consumption. Thus appropriate temperature monitoring is a crucial task. So we developed a Smart Temperature monitoring system using the temperature & humidity sensor module DHT11 which comprises a resistive element & a sense of wet NTC temperature measurement device, with a high performance 8 bit Microcontroller connected inside the DHT11 MODULE. For IoT and Smart connectivity we are using WiFi modules (ESP8266) and GSM modules (SIM800L) which are connected to our host MCU (STM32F103). Both the IoT modules can be configured in Web Client Mode and web server mode to send data to Remote Server (like Thingspeak or AWS) and send data locally by connecting a local webclient on the dedicated IP address. Validation of smart temperature data logger has been done on the real time data that this device monitors the Temperature upto 2 percent accuracy and very efficiently logs the temperature readings of medicine and sends the data to WebServer.